Well-Designed Food Governance as Psychological Mechanism of Consumer Perceptions in the Context of Tourism Poverty Alleviation - Huang, Guo-qing; Lin, Kuen-Lin (Frontiers in Psychology, 2021)
Poverty is a challenge leading to food insecurity in people's minds. This article discusses food governance as a psychological mechanism to facilitate the sense of wellness in people's minds in the context of tourism poverty alleviation. Mainly, we argue that, when a government is implementing tourism poverty alleviation, not only are economic efforts, but also positive psychological feelings are required. We, thus, argue that sound food governance may increase the sense of wellness in the minds of people as food consumers by increasing food safety and security. This perspective paper contributes by explicating the influences of macrolevel governance design of safer and more secure food systems on people's psychological wellness, especially against the background of tourism poverty alleviation in developing countries.